2022
DOI: 10.3389/fcvm.2022.834879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Orthostatic Syncope and Presyncope on Quality of Life: A Systematic Review and Meta-Analysis

Abstract: PurposeSyncope (transient loss of consciousness and postural tone) and presyncope are common manifestations of autonomic dysfunction that are usually triggered by orthostasis. The global impact of syncope on quality of life (QoL) is unclear. In this systematic review, we report evidence on the impact of syncope and presyncope on QoL and QoL domains, identify key factors influencing QoL in patients with syncopal disorders, and combine available data to compare QoL between syncopal disorders and to population no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Intriguingly, general fatigue severity was not related to disease severity in patients with POTS, inferred from the magnitude of the heart rate increment observed during head up tilt. This is in keeping with previous observations that the orthostatic heart rate response is also not a good predictor of quality of life in patients with POTS [8,75]. Healthcare providers should not overlook the possibility for severe fatigue in patients with POTS, even those with less severe orthostatic tachycardia.…”
Section: Fatigue Severity Scale Scoressupporting
confidence: 90%
See 2 more Smart Citations
“…Intriguingly, general fatigue severity was not related to disease severity in patients with POTS, inferred from the magnitude of the heart rate increment observed during head up tilt. This is in keeping with previous observations that the orthostatic heart rate response is also not a good predictor of quality of life in patients with POTS [8,75]. Healthcare providers should not overlook the possibility for severe fatigue in patients with POTS, even those with less severe orthostatic tachycardia.…”
Section: Fatigue Severity Scale Scoressupporting
confidence: 90%
“…The association between fatigue and mental health is not clear, but it has been suggested that it reflects that many people with POTS suffer from sleep disturbance, pain, fatigue and brain fog, which can severely diminish quality of life and lead to suicidal ideation [42]. Psychiatric comorbidities are also noted in patients with VVS, with a higher prevalence than healthy controls [8,73]. Whether this also reflects an association between fatigue and mental health concerns in patients with other orthostatic syncope disorders is unclear.…”
Section: Fatigue Severity Scale Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially noteworthy, as the role of CPM in syncope management is not necessarily to eliminate episodes all together. Patient quality of life is inversely related to episode frequency ( 12 ), therefore reducing episodes could still lower syncope burden, bringing a substantial benefit to the patient ( 90 , 96 ). Over a 1-year follow up, Romme et al reported that while 49% of patients experienced a syncopal recurrence, disease-specific quality of life improved most in patients with the largest reductions in syncope burden (as quantified by episode frequency over time) ( 96 ).…”
Section: Counter Pressure Maneuversmentioning
confidence: 99%
“…Up to 30% of those who have fainted will experience recurrent and severe episodes (7). Living with recurrent syncope presents many challenges to daily living, and can profoundly impact patient independence, and quality of life (8)(9)(10)(11)(12). Patients with syncope also face greater fatigue in daily living (13), and an increased risk of fall-related injury associated with their loss of consciousness, particularly in older adults with increased frailty (14,15).…”
Section: Introductionmentioning
confidence: 99%